Single-center register of myocardial revascularization in patients with coronary artery disease and acute coronary syndrome in the context of COVID-19 pandemic - O. V. Kamenskaya; A. S. Klinkova; I. Yu. Loginova; V. N. Lomivorotov; A. M. Chernyavskiy; V. V. Lomivorotov (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To assess the short- and long-term outcomes of myocardial re- vascularization (MR) in patients with coronary artery disease (CAD) and acute coronary syndrome (ACS) in the context of coronavirus disease 2019 (COVID-19) pandemic.Material and methods. In the period from April to August 2020, 550 patients with CAD and ACS were included in the register. Emergency percutaneous transluminal coronary angioplasty (n=499) and on-pump coronary artery bypass grafting (CABG) (n=51) were performed. The follow-up period lasted 6 months. The pattern of complications after MR and effects of COVID-19 were analyzed.Results. The studied cohort is represented by patients with CAD >65 years old. ST segment elevation ACS was detected in 23%, acute myocardial infarction — in 59,1%, in other cases — unstable angina. During hospitalization after MR, atrial fibrillation prevailed among cardiovascular complications (4,7%). During this period, 29 (5,3%) patients was diagnosed with COVID-19. In the short-term period after MR, 3 (0,5%) people died due to COVID-19 complications-. In the long-term period after MR, 4 (0,7%) cases of non-fatal stroke were registered, while repeated MR — in 7,1%. The all-cause mortality rate was 1,3% (n=7), of which 57,1% of patients died due to COVID-19 complications. In the subgroup of patients who underwent CABG, the greatest number of in-hospital complications was noted, where exudative pleurisy, atrial fibrillation and anemia prevailed. Of the patients with COVID-19, pneumonia in the short-and long-term posto perative periods was recorded in 48,3 and 61,3%, respectively. Pneumonia is associated with respiratory failure, cardiac dysfunction, and anemia. The risk of COVID-19 pneumonia during the entire follow-up period was higher in patients with ACS who underwent CABG (odds ratio, 19,4; confidence interval: 13,3-26,1; p<0,001). The overall survival rate was 98,7%.Conclusion. COVID-19 infection in patients with ACS after MR effects pattern of postoperative complications. The proportion of COVID-19 pneumonia in patients with ACS in hospital, short-  and long-term postoperative periods after MR significantly exceeds that in the general population. The leading factor associated with COVID-19 pneumonia in patients with ACS is on-pump CABG.